IMPLEMENTASI METODE TALAQQI DALAM MENINGKATKAN KUALITAS HAFALAN AL-QUR’AN SANTRI SEKOLAH ADAB MIM BALEHARJO - Ratna Agus Rahmawati; Septyana Tentiasih (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Memorizing the Qur'an (tahfidz) is a fundamental component of Islamic education that contributes significantly to a Muslim's spiritual and intellectual growth. However, in practice, many students (santri) encounter challenges in the memorization process, including difficulties with concentration, the use of less effective methods, and limited time available for focused memorization. This study aims to examine the implementation of the talaqqi method in improving the quality of Qur'an memorization among students at Adab Madrasah Ibtidaiyah Muhammadiyah Baleharjo, Pacitan. The talaqqi method is a learning approach in which students engage directly with the teacher through listening, imitating, and receiving immediate correction of their recitation. This research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The findings reveal that the application of the talaqqi method enhances the quality of students' memorization, particularly in term of accurate tajwid and makhraj (pronunciation), fluency, and proper etiquette in reciting the Qur'an. Supporting factors identified include a conducive learning environment, strong student motivation and discipline, support from parent and the surrounding community, and a structured learning system. On the other hand, inhibiting factors include low motivation and inconsistency among students, limited instructional time, variations in students' abilities, inadequate facilities and infrastructure, and insufficient repetition (muraja'ah).